Shear Motion Characteristics Analysis of Electrorheological Fluids Between Flat Disk and Corrugated Disk - Li, Chunyu; Chen, Bingsan; Huang, Yijian (Frontiers in Materials, 2022)
In order to improve the transmission torque caused by the electrorheological effect, a corrugated disk is proposed to replace traditional flat disk by changing the electrode surface shape. The new mechanism puts the device in a shear-squeeze mode of operation. Based on the constitutive equation of electrorheological fluids, the shear motion characteristics of the ER fluids between the flat disk and the corrugated disk are analyzed, including the pressure distribution, torque equations, and the comparison with double-flat-disk mechanism. The analysis shows that compared with the double-flat-disk structure, the flat-disk-corrugated-disk structure can enhance the transmitted torque over 2.6 times under the same operating parameters. The magnification of the torque is not related with the curve number of the corrugated disc, but mainly depends on the structural parameters of the device and corrugations, and the characteristic parameters of electrorheological fluid. It is proved that the mechanism can provide new ideas and new methods for the engineering application of electrorheological transmission technology.